An Analysis of Affecting Factors for The Community Income Levels around Steam Fired Power Plant (PLTU) Paiton: Case Study in Binor Village, Paiton Subdistrict, Probolinggo Regency, Indonesia - Hayatul Millah; Hikmatul Maufidah; Abdul Komar (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2019)
The purpose of this research is to determine the effect on education variables, length of work (work experience), and gender on the level of income of the community around the PLTU Binor in Paiton Subdistrict, Probolinggo Regency, to determine the variables that had the most dominant influence on the income level of the surrounding community PLTU Binor in Paiton Subdistrict, Probolinggo Regency. The type of this research is a quantitative research. The analysis method that uses in this research is multiple linear regression. The sampling method in this research is simple random sampling technique. The samples that uses in this research amounting to 90 respondents. The results of this research showed that the education variables, length of work (work experience), and gender have a positive and significant effect on the income levels of the community around the PLTU Binor in Paiton Subdistrict, Probolinggo Regency. The most dominant variable influencing the income level of the community around PLTU Binor, Paiton Subdistrict, Probolinggo Regency is an education variable.